Multi-scale distributions and movements of fish communities in tributaries to the San Juan River - Cathcart, Charles Nathan (Kansas State University, 2014)
Recognizing habitat needs of fishes across space and time is increasingly important for managing altered stream networks, such as in the Colorado River basin. Recent work on warm-water fishes suggest they might benefit from access to tributaries and their confluences. Fish movements or distributions within tributaries relative to distance from mainstem confluences in two streams with different network types (linear versus dendritic) were investigated in the San Juan River basin, USA. Upstream distance from the San Juan River resulted in species declines (Chaco Wash, linear network) or turnover (McElmo Creek, dendritic network). McElmo Creek movement patterns were likely attributed to spring spawning migrations of flannelmouth sucker (Catostomus latipinnis), spawning aggregations of razorback sucker (Xyrauchen texanus), foraging or refuge seeking by Colorado pikeminnow (Ptychocheilus lucius), and monsoon-related movements for channel catfish (Ictalurus punctatus) and razorback sucker. Razorback sucker and Colorado pikeminnow dominated movements at Chaco Wash, suggesting this backwater-like tributary supplied thermal or current refuge, foraging habitat, or both. Within McElmo Creek, a second study explored the importance of confluences by characterizing habitat use and movements of fishes at the junction of McElmo and Yellow Jacket creeks. Native fish dominated the confluence community composition. The reach downstream of the confluence had consistently higher abundances, species richness, and more frequent detections of tagged fishes relative to upstream reaches. Movement behaviors inferred by detection frequency of tagged fish among reaches surrounding the confluence differed among species. Small flannelmouth sucker (< 300 mm) and roundtail chub (Gila robusta) were commonly detected in Yellow Jacket Creek whereas large flannelmouth sucker (> 300 mm), bluehead sucker (C. discobolus), and channel catfish used McElmo Creek reaches. Monsoons increased McElmo Creek discharge which triggered upstream movements of channel catfish and displaced large flannelmouth sucker and bluehead sucker. Monsoons increased movements between McElmo and Yellow Jacket creeks by roundtail chub, small flannelmouth sucker, and black bullhead (Ameiurus melas). Combined, these two field studies emphasized using links between patterns and processes of tributary fish communities. Conservation, rehabilitation, and maintenance of connectivity and habitat heterogeneity at confluence zones likely can be a localized management strategy with expansive ecosystem effects.
Keywords: San Juan River; Fish ecology; Movement; Fish; Endangered species; Biology (0306); Ecology (0329)